Efektivitas Pembekalan Materi Kesehatan Reproduksi Tentang Bahaya Pernikahan Dini Untuk Remaja Putri - Fardila Elba; Merry Wijaya (Sehat MasadaJurnal, 2020)
Early marriage is still a major concern for women's health in Indonesia. The lack of information on the dangers of early marriage make adolescents do not understand the consequences, so they took the decision to marry early without considering the risk. This study aims to find out the effectiveness of reproductive health material supply about the dangers of early marriage of girl adolescents' knowledge Quantitative study one group pre- and post-test pre-experimental design, done in the Kalisari Village, Karawang Regency, in May 2018. The population consists of 316 girl adolescents. Sample a number of 101 people elected by proportionate stratified random sampling. Data source derived from primary data (questionnaire) and secondary data (book-keeping register of annual reports on the KUA). The data were analyzed using paired T-test and calculation of the effect size (ES). The results show that the pre-test score (R = 66.14, SD = 15.38) increase to a post-test score [R = 76.36, SD = 16.10, t (101) = 7.65, p = 0000]. The intervention has great effectiveness (ES ≥ 0.14) towards increased knowledge of girl adolescents about the dangers of early marriage (ES = 0.37). Reproductive health material supply about the dangers of early marriage is effective to increase the knowledge of girl adolescents.